A healthy lifestyle during adolescence was inversely associated with fatty liver indices in early adulthood: findings from the DONALD cohort study. Issue 3 (14th February 2023) - Schnermann, Maike Elena; Schulz, Christina-Alexandra; Perrar, Ines; Herder, Christian; Roden, Michael; Alexy, Ute; Nöthlings, Ute
Abstract: A healthy lifestyle during adolescence is associated with insulin sensitivity or liver enzyme levels and thus might contribute to the prevention of non-alcoholic fatty liver disease (NAFLD). Therefore, we examined the association between adherence to a hypothesis-based lifestyle score including dietary intake, physical activity, sedentary behaviour, sleep duration and BMI in adolescence and fatty liver indices in early adulthood. Overall, 240 participants of the DOrtmund Nutritional and Anthropometric Longitudinally Designed study completed repeated measurements of lifestyle score factors during adolescence (females: 8·5–15·5 years, males: 9·5–16·5 years). Multivariable linear regression models were used to investigate the association between adolescent lifestyle scores and NAFLD risk (hepatic steatosis index (HSI) and fatty liver index (FLI)) in early adulthood (18–30 years). Participants visited the study centre 4·9 times during adolescence and achieved on average 2·8 (min: 0·6, max: 5) out of five lifestyle score points. Inverse associations were observed between the lifestyle score and fatty liver indices (HSI: ß=−5·8 % (95 % CI −8·3, −3·1), P < 0·0001, FLI: ß=−32·4 % (95 % CI −42·9, −20·0), P < 0·0001) in the overall study population. Sex-stratified analysis confirmed these results in men, while inverse but non-significant associations were observed in women ( P > 0·05). A higher lifestyle score was associated with lower HSI and FLI values, suggesting that a healthy lifestyle during adolescence might contribute to NAFLD prevention, predominantly in men. Our findings on repeatedly measured lifestyle scores in adolescents and their association with NAFLD risk in early adulthood warrant confirmation in larger study populations.